2013
DOI: 10.1136/emermed-2012-202005
|View full text |Cite
|
Sign up to set email alerts
|

‘Out of hours’ adult CT head interpretation by senior emergency department staff following an intensive teaching session: a prospective blinded pilot study of 405 patients

Abstract: In conclusion, we feel that this model can be employed as a safe and long-term alternative provided that the radiology department are committed to providing ongoing teaching and that a database is maintained to highlight problem areas. Emergency physicians need to remember that the clinical status of the patient must never be ignored, irrespective of their CT head findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…In studies that compare many patient groups' cranial CT interpretations, a concordance of between 60% and 94% was found between EPs and radiologists (9)(10)(11)(12)(13)(14). In our study, this rate was found to be 93.6%.…”
Section: Discussionsupporting
confidence: 53%
“…In studies that compare many patient groups' cranial CT interpretations, a concordance of between 60% and 94% was found between EPs and radiologists (9)(10)(11)(12)(13)(14). In our study, this rate was found to be 93.6%.…”
Section: Discussionsupporting
confidence: 53%
“…For plain radiographs, a few large single‐center studies report discrepancies ranging from 1% to 7% . For CT, there was good agreement for renal disease on noncontrast CT (κ > 0.75), high agreement (94% concordance) for head CT after an educational intervention, and poor agreement for chest CT for pulmonary arteries (sensitivity 54%, specificity 57%) . However, the goal of interpretation for EPs often differs from that of radiologists.…”
Section: Consensus Resultsmentioning
confidence: 99%
“… 1 , 2 This is particularly true in practice settings that do not have attending radiologists in house at all times. 10 , 30 , 31 Nonetheless, the skill of head CT interpretation exists in a border region of knowledge domains between clinical specialties. As educators, this forces us to consider the complex issue that teaching one topic to sufficient depth can come at the expense of time for other topics in residency education.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies addressed this knowledge gap using onetime didactic lectures or instructional videos. [8][9][10][11][12] However, demonstrating CT findings on single images poorly represents the cognitive work of identifying these findings in clinical practice. 13 Even if a lecturer "scrolls" through a CT, learners are unable to actively engage with the images.…”
Section: Discussionmentioning
confidence: 99%